PDE5 inhibitors against synaptic and cognitive impairment in Alzheimer's disease and related dementia. (20th December 2022) - Arancio, Ottavio; Zuccarello, Elisa; Fiorito, Jole; Acquarone, Erica; Argyrousi, Elentina; Staniszewski, Agnieszka; Calcagno, Elisa; Puzzo, Daniela; Deng, Shi‐Xian; Landry, Donald
Abstract: Background: Gene transcription mechanisms leading to synaptic plasticity and memory formation, including phosphorylation of the transcription factor CREB, are perturbed in Alzheimer's disease (AD). In this regard, cyclic guanosine monophosphate (cGMP), which activates cGMP‐dependent protein kinases that, in turn, phosphorylate CREB, has been implicated in the memory and synaptic plasticity impairment occurring in the disease. Sildenafil (Viagra ® ), the well‐known FDA approved inhibitor of phosphodiesterase 5 (PDE5I), the enzyme that degrades cGMP, has shown efficacy in AD animal models (Zuccarello et al, Biochem Pharmacol. 2020) and was recently significantly associated with a reduced risk of AD in an unbiased study including 7.23 million individuals (Fang et al, Nat. Aging 2020). Method: Following the development of a library of small molecules inhibiting phosphodiesterase 5 (PDE5), compound efficacy was tested in different animal models of Aβ and tau elevation. Specifically, these animals were tested using a combination of biochemical (western blotting of proteins involved with gene transcription machinery), electrophysiological [analysis of long‐term potentiation (LTP), a type of synaptic plasticity thought to underlie memory formation], and behavioral (assessment of spatial and associative memory through radial arm water maze and fear conditioning) techniques. Result: Structure activity relationship (SAR) analysis of existing PDEI scaffolds led to the design and synthesis of compound 7a, a quinoline customized for AD with improved physiochemical properties compared to existing inhibitors. The molecule has outstanding inhibitory activity against PDE5 (IC50 = 0.27nM) and selectivity against all other PDE isoforms (PDE5/PDEs > 1000). It also crosses the blood brain barrier (AUC0‐t ratio = 0.41) and has similar Tmax values in the brain and plasma, indicating that its distribution to the brain is fast. Moreover, similar to other PDE5Is, 7a re‐established normal LTP and both spatial and associative memory after Aβ and tau elevation. Finally, the compound re‐established normal increase of CREB phosphorylation and cGMP levels after memory induction in the presence of Aβ and tau. Conclusion: Up‐regulation of CREB activation through PDE5 inhibitors might be beneficial against Aβ and tau‐induced synaptic and memory dysfunctions.